THE INFLUENCE OF SOCIAL MEDIA USE AND MOTIVATION ON STUDENTS' ENTREPRENEURIAL INTERESTS - Hermisya, Nanine Ivana; Purwana, Dedi; Munawaroh (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
The purpose of this study was to determine the level of use of social media and motivation to interest in entrepreneurship. This research was conducted on 2017-2018 students majoring in Business Creative Industry, Kalbis University. This study requires a sample of 127 students. The method used is quantitative. Researchers used 3 variables, Interest in Entrepreneurship (Y), Use of Social Media (X1) and Motivation (X2). The results of the normality test obtained values of Interest in Entrepreneurship (Y) 0.133, Use of Social Media (X1) 0.200, and Motivation (X2) 0.129. for the linearity test Deviation From Linearity shows the number 0.164 in the X1 test against Y, while for the X2 test against Y it is 0.56. Second, Classical Assumption Test which consists of Multicollinearity Test and Heteroscedasticity Test. Multicollinearity test (p-value tolerance > 0.1; p-value VIF < 10) obtained for the tolerance value for X1, X2 of 0.360, 0.360, while for the VIF value of X1, X2 of 2.776, 2.776. Spearmans' Rho Heteroscedasticity Test Results (p-value > 0.05) obtained X1, X2 values of 0.326, 0.461. The three multiple regression tests with the equation Y = 0246 + 0.220 X1 + 0.690 X2. Fourth, the hypothesis test which consists of the F test and t test. for the F test, the value of F-count is 169.135 > F-table 3.07. For the T-test, the value of T-count is 2.687 > T-table 1.97928. Fifth, the Coefficient of Determination Analysis (R2) obtained an R2 value of 0.732.